Exploration of Self-Efficacy Based on Students' Mathematical Representation Ability In Problem Solving SPLDV - Hadi, Heri Sopian; Assa'ady, M. Chothibul Umam; Irhas, Irhas (Universitas Nusantara PGRI Kediri, 2024)
Aim for know ability representation mathematical in finish questions on the material system linear equations of two variables (SPLDV) are reviewed of student self-efficacy class VIII SMPN 1 Praya Timur. As for Sujek in study This consists of 3 of 28 students class VIII which has categories of high self-efficacy, medium self-efficacy and low self-efficacy. Types of research This is study qualitative descriptive. Instruments used​ in study This is questionnaire, question test ability representation mathematics and guidelines interview. Procedure data collection used in study This that is documentation and interviews. Data analysis techniques were carried out with method reducing data, presenting data, and interesting conclusion. Checking validity of the data used triangulation technique. Research result show that ability representation mathematical student class VIII SMPN 1 Praya Timur is divided into 3 (three) categories, namely student with high self-efficacy category capable shows 3 aspects ability representation mathematical that is visual representation, representation equality or expression mathematics, and representation of words or text written, whereas student with moderate self-efficacy category only capable shows 2 aspects ability representation mathematical that is representation equality or expression mathematics, and representation of words or text written. Temporary That student with low self-efficacy category only Can shows 1 aspect ability representation mathematical that is representation equality or expression mathematical.